Drugs Act 1978 of Nepal: A Critical Analysis - Pathak, Nabin; Basyal, Bijaya; Jha, Prabhat Kumar; Yadav, Ujjwal; Karki, Badri; Jha, Supriya; Chalise, Mamata; Kunwar, Nisha; Adhikari, Samikshya; Ojha, Sabita; Giri, Anil (Journal of Karnali Academy of Health Sciences, 2022)
Background: With the enactment of the Drug Act in 1978, through the establishment of different bodies underthe act, drug-related activities have been regulated and controlled in Nepal so as to provide safe and efficaciousdrugs of standard quality to the general public. However, with the overgrowing use of drugs, cosmetics,biotechnological products, nutraceuticals, and veterinary products in the present market and the present actfailing to include these aspects, this paper tries to critically analyze the Drug Act 1978 of Nepal which willcomprise strengths, weaknesses, opportunities, and threats faced in current scenario regarding the act. Theregulation of drugs in Nepal was started with the enactment of the Drugs Act in 1978 AD, which is beingcarried out by the Department of Drug Administration as provisioned in the section 5 of the act. To facilitatethe proper implementation of the act, various rules, regulations and guidelines are framed. The objective ofthis study was to explore the areas to improve in the Drugs Act and help foster the use of safe, efficacious andquality drugs.Method: The Drugs Act 1978 was critically analyzed focusing on the strengths, weaknesses, opportunities,and threats of the act as of current scenario.Result: After critically analyzing the drugs act 1978 we found out that there is lack in regulations of use ofcosmetics, newer biotechnology products, nutraceuticals, veterinary product, innovative pharmaceuticalproducts as well as the online pharmacy services.Conclusion: A major amendment and periodic revision is required with the consequence of meeting timelyneeds and promoting the idea of safety and efficacy in drug related activities.